Primary lymphangioma circumscriptum around external urethral meatus in a male child: A rare presentation - Jayanti Singh; Surabhi Dayal; Janshruti Mothsra; Priyadarshini Sahu (Wolters Kluwer Medknow Publications, 2020)
Primary lymphangioma circumscriptum (LC) is a superficial lymphatic malformation, presenting as multiple fluid-filled grouped vesicular lesions which may be associated with slight hemorrhages. We report a rare case of primary LC with exclusive involvement of area around the external urethral meatus in a 10-year-old male child. We treated the patient with radiofrequency ablation under topical anesthesia with eutectic mixture of local anesthetics (EMLA). No recurrence has been observed in the past 1 year. LC must be included in differentials when presented with vesicular lesions near the external urethral meatus in male pediatric patients.